KARAKTER FORMAL BANGUNAN 01 KAMPUS UNY KARANG MALANG - Ikhwanuddin Ikhwanuddin (Universitas Negeri Yogyakarta, 2006)
ABSTRACTThe Karangmalang campus of Jogjakarta State University is a continuously developed area. At least, it can be seen from the appearance of some new buildings in these area. It is a good thing, but in the other, some worries appear as those new buildings were designed imperfectly. It seems that those new buildings were designed in different sight one to another..